Work Motivation and Principal Supervision Perception: Effects on Teacher Performance - Sumantri, Sumantri; Mahmud, Hilal; Shaleh, Mahadin (International Journal of Asian Education, 2024)
Teachers are a key element in the education system. Other components, such as curriculum, infrastructure, and funding, become meaningless without quality teachers. This study aims to analyze the influence of teachers' work motivation and their perception of school principal supervision on teacher performance at SMPN 1 Bone-Bone. The research employs an ex-post facto design with a population of 49 teachers. All are included as samples (total sampling). Data were collected via a questionnaire covering work motivation, perception of supervision, and teacher performance and analyzed using multiple linear regression. The results show that teachers' work motivation and perception of school principal supervision are in the medium category, with average scores of 90.531 and 71.571, respectively. Teacher performance varies more widely, with an average score of 142.367. Regression analysis indicates a significant influence of work motivation and perception of school principal supervision on teacher performance. These findings highlight the importance of enhancing teachers' work motivation and the quality of school principal supervision to improve teacher performance, suggesting strategies such as professional development, recognition, and support from school principals.